Guanxi, Mianzi, and Business : The Impact of Culture on Corporate Governance in China - Smith, David (World Bank, Washington, DC, 2014)
Before taking advantage of the growing opportunities of the Chinese market, investors will do well to understand the strong influence of Chinese culture on the way businesses operate, how they govern themselves, and how they interact with each other. The author (David Smith) identifies two key cultural and sociological issues of particular interest guanxi (relationships and networks) and mianzi (face). He analyzes their most common implications for investors in areas such as related-party transactions, board composition and deliberations, and shareholder engagement.